2019
DOI: 10.1029/2019jd030481
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Trends and Impacts on Vegetation Greening Over the Tibetan Plateau

Abstract: The Tibetan Plateau (TP) is an ecologically fragile region that is sensitive to climate change. In the context of global climate change, the climate change trends of the TP and the vegetation dynamic response need to be investigated. Based on in situ meteorological data, Satellite Pour l'Observation de la Terre vegetation data, and Moderate Resolution Imaging Spectroradiometer land cover data, a comprehensive analysis was conducted to determine the trends of climate parameters in the TP region at different tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 46 publications
5
62
0
Order By: Relevance
“…Overgrazing has degraded pastures, resulting in an increase in exposed ground, which has increased the solar radiation absorbed by the ground and its LST. Regarding the Qinghai-Tibet Plateau, Zhong et al [44] pointed out that while discerning natural and anthropogenic effects on vegetation dynamics is difficult, a significant increase in barren land was observed in this region. Huang et al [45] investigated the impact of human intervention on the vegetation of the Qinghai-Tibet Plateau and reported that after 2000, the significant increase in human activities seriously affected the vitality of the vegetation in this region.…”
Section: ) Correlation Analysis Between Annual Mean Lst and Ndvi_maxmentioning
confidence: 99%
“…Overgrazing has degraded pastures, resulting in an increase in exposed ground, which has increased the solar radiation absorbed by the ground and its LST. Regarding the Qinghai-Tibet Plateau, Zhong et al [44] pointed out that while discerning natural and anthropogenic effects on vegetation dynamics is difficult, a significant increase in barren land was observed in this region. Huang et al [45] investigated the impact of human intervention on the vegetation of the Qinghai-Tibet Plateau and reported that after 2000, the significant increase in human activities seriously affected the vitality of the vegetation in this region.…”
Section: ) Correlation Analysis Between Annual Mean Lst and Ndvi_maxmentioning
confidence: 99%
“…The TP has experienced significant climatic warming over the past five decades (Lu and Liu, 2010;Cai et al, 2017;Zhong et al, 2019), and the warming has accelerated since the 1980s (Lu and Liu, 2010;Zhong et al, 2019). The mean annual temperature has increased faster in the northeastern and northwestern areas than in the southeastern areas of the TP over the past five decades (Li et al, 2010;Deng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Annual precipitation has increased substantially in the western, central, and northeastern areas but has decreased slightly along the southeastern and southwestern edges of the TP over the past 40 years (Zhang et al, 2017). Climatic change has resulted in substantial changes in the growth of vegetation across the TP (Piao et al, 2012;Lehnert et al, 2016;Zhu et al, 2016;Zhang et al, 2018;Zhong et al, 2019). For instance, climate warming not only advanced vegetation green-up date but also extended the length of the growing season across the TP (Liu et al, 2006;Piao et al, 2011;Dong et al, 2012) Shen et al (2016 have reported that nighttime warming advanced vegetation green-up date in most area across the TP, likely nighttime warming reduced low temperature constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research progress has been achieved in studying vegetation dynamics under climate changes in arid, semiarid and semi-humid regions by using the satellite earth observation time-series data, for example the Normalized Difference Vegetation Index (NDVI) data [5,[10][11][12]. Studies in the Tibetan Plateau region have found that vegetation cover has mainly been affected by climatic factors and increased as temperature and precipitation increased [13,14]. In central Asia, precipitation has been identified as the main factor driving vegetation growth, while temperature has been identified as a control variable for vegetation greenness [11,15,16].…”
Section: Introductionmentioning
confidence: 99%